Addressing the Growing Risks of Nuclear Use in East Asia - Jon B. Wolfsthal; Toby Dalton (Journal for Peace and Nuclear Disarmament)
The role of nuclear weapons is growing globally, but nowhere more so than in and around East Asia. Four nuclear weapons states are located and active in the region, and several non-nuclear states are reliant on extended nuclear deterrence for their security. The regional, military and geostrategic dynamics are all pointing toward increased nuclear risks – both through deliberate or accidental use. The authors of this piece coordinated a year-long research project with experts on the nuclear policies and views in Japan, the Republic of Korea, the People’s Republic of China, the Russian Federation and the United States of America. The results of these efforts are included in a series of articles published in the Journal for Peace and Nuclear Disarmament and the major themes and conclusions are presented here by the two project leads.